2008
DOI: 10.3382/ps.2008-00023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forsythia suspensa Extract on Growth Performance, Nutrient Digestibility, and Antioxidant Activities in Broiler Chickens Under High Ambient Temperature

Abstract: A 42-d trial was conducted with 252 broiler chickens (d 1 of age, 38.8 +/- 1.3 g of BW) to determine the effects of Forsythia suspensa extract on growth performance, nutrient digestibility, and antioxidant activities under high ambient temperature (32 +/- 1 degrees C). The feeding program consisted of a starter diet from d 1 to 21 of age and a finisher diet from d 22 to 42 of age. Dietary treatments included a negative control group (NC) fed a cornsoybean meal based diet without vitamin C or Forsythia suspensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 25 publications
5
74
1
1
Order By: Relevance
“…The phenolic and flavonoid contents were lower than data reported by other authors (Wang et al, 2008;Ghasemi et al, 2009), e.g. using similar analytical methods.…”
Section: Composition Of Citrus Peel Extractscontrasting
confidence: 52%
“…The phenolic and flavonoid contents were lower than data reported by other authors (Wang et al, 2008;Ghasemi et al, 2009), e.g. using similar analytical methods.…”
Section: Composition Of Citrus Peel Extractscontrasting
confidence: 52%
“…Studies have indicated that the body can produce reactive oxygen species under heat stress (Khar et al, 2006;Del Vesco and Gasparino, 2013), and the antioxidant activity of tissues can be determined by measuring the activity of SOD and GSH-PX, and MDA content in tissues (Wang et al, 2008;Starrs et al, 2001). In this study, we found a significant difference in the total SOD activity in the BF tissue among the three groups in week 3 and 6 only.…”
Section: Z Chen Et Al: Effects Of γ -Aminobutyric Acidmentioning
confidence: 99%
“…Curry leaves have also shown anti-oxidative activity, immunomodulatory activity, hepatoprotective activity and antiinflammatory activity (Jain et al, 2012). Dietary antioxidants supplement suggested as efficient way to reduce heat stresses and improve growth performances in broilers (Wang et al, 2008). Hence, the supplementation of curry leaves powder in this study might reduce broiler oxidative stress, enhanced oxidative stability via reduce oxidative free radicals and balance in antioxidant status.…”
Section: Performance Of the Birdmentioning
confidence: 99%
“…Correspondingly, our presenting data for feed intake observed no difference (P>0.05), when broiler fed diet supplemented with curry leaves with same energy level and nitrogen level from 1 to 32 days of age. Contradictory was reported, supplementation of antioxidant improved feed intake of broiler reared under high ambient temperature (Wang et al, 2008).…”
Section: Performance Of the Birdmentioning
confidence: 99%